Ceratoplastia lamelar em coelhos usando enxerto de omento alï¿½geno livre e cï¿½lulas mesenquimais omentais associadas com membrana amniï¿½tica canina - De Barros, Sï¿½fora Vieira Da Silva Gouvï¿½a [UNESP]; Aldrovani, Marcela [UNESP]; De Lacerda, Luciana Cenï¿½o Correa [UNESP]; Horr, Mï¿½nica [UNESP]; Marinho, Fï¿½bio Andrade [UNESP]; Lima, Tiago Barbalho [UNESP]; Da Silveira, Camila Pinho Balthazar [UNESP]; Brito, Fï¿½bio Luiz Da Cunha [UNESP]; Bassaneze, Vinï¿½cius; Flecher, Mayra Cunha; Beltrame, Renato Travassos; Nakamuta, Juliana Sanajotti; et al. (FapUNIFESP (SciELO), 2016)
The objective of this research was to evaluate the clinical and microscopic effects in rabbits of lamellar keratoplasty using allogeneic omentum associated with canine amniotic membrane (AM). Rabbits were divided into two groups: one received the allogeneic free omental graft covered with the AM (OM-graft group), while the other received the AM graft containing omental mesenchymal cells (OM-cell group). Clinical signs were evaluated on different postoperative days. After the clinical assessments, the rabbits were euthanized and their corneas were obtained for histopathology and immunohistochemistry (Ki-67, marker for proliferation). Both groups showed chemosis, blepharospasm, eye discharge, hyperemia, and corneal opacity/ edema. Neovascularization was observed in the OM-cell group. Histopathological evaluation revealed epithelial islands within the stroma of OM-cell samples. Thirty days after surgery, complete corneal re-epithelialization had occurred in both groups. The OM cell group showed more Ki-67 positive cells. The free omentum and its cells, combined with the AM, contributed to corneal repair, a process that was completed 30 days after lamellar keratoplasty.
Lamellar keratoplasty in rabbits using an allogeneic free omental graft and omentum-derived mesenchymal cells associated with the canine amniotic membrane
Keywords: Amniotic membrane; Cornea; Omentum; Progenitor cells; Wound healing